"Bridge" project: An intergenerational approach with prototype games for young people and people with dementia: Other innovative programs and practices. (7th December 2020) - Tsolaki, Magda; Makri, Marina
Abstract: Background: People with dementia (PwD) are often excluded from intergenerational social activities due to stigmatization. The generation gap is constantly widening while young people are losing their interest to participate in volunteering actions concerning elderly people. The Erasmus+ funded "Bridge" program is a 3 year pan‐European initiative that aims to develop a set of prototypes Serious Games (SGs) (physical, digital or phygital) acting on cognitive and behavioral symptoms of dementia, involving also younger and older people. Method: A Methodological Guide related to Bridge's workshops methodology, key points for prototype SGs and e‐platform was developed. This step was followed by Co‐Creation Workshops in 3 countries, development of working games prototypes and finalization of 8 selected games. A second Implementation of Workshops will be organized in each country in order to figure out these results. The Bridge web‐platform (https://projectbridge.eu/ ), containing MOOCs on the methodology of the game‐creation workshops and the final 8 selected prototypes games will be the final result. Results: In the Methodological Guide, the Bridge workshops and the game co‐design process is defined. In Greece (Alzheimer Hellas), Italy (Anziani e non solo) and Romania (Asociatia Habilitas), 24 PwD co‐designed and played several games in collaboration with 6 game‐designers, 16 healthcare professionals, 7 caregivers and 21 young volunteers. After the implementation of the workshops 11 prototypes of the games have been developed. The team project decided which of them can be the final 8 games for the Bridge platform, which have been refined through and digitalized. The final 8 prototypes games are: Next destination, flea market, find the word, bird‐watching, emotions, the directors, blooming flowers, speciatite. Conclusion: The intergenerational workshops, in which PwD and young people create and use SGs, can narrow the gap between generations, decrease the stigma of dementia and promote civic participation of young people by developing the role of volunteering for social inclusion. This intervention and the final result of this program can create awareness and motivation about importance and possibilities of SGs as a tool for improving the quality of life of older people and their families and improve cognitive and behavioral dysfunctions of PwD.